Achieving enhanced toughness of a nanocomposite coating by lattice distortion at the variable metallic oxide interface. (December 2022) - Zhang, Zhen; Yang, Zehui; Qian, Weifeng; Chen, Yongnan; Xu, Yiku; Xu, Xiqing; Zhao, Qinyang; Li, Hongzhan; Zhao, Yongqing; Zhan, Haifei
Graphical abstract: Highlights: A toughened ZrO2 /MgO nanocomposite coating is in-situ synthesized during the plasma electrolytic oxidation process (PEO). The ZrO2 /MgO toughening behavior occurs with dislocation slipping and pinning caused by semicoherent interface lattice distortion. The toughness (KIC ) of the ZrO2 /MgO nanocomposite coating is 2.7 times that of the traditional PEO coating. Abstract: Ceramic coatings are in general a kind of brittle material because they are predominantly made up of ionic crystals that avoid dislocation motion caused by lattice distortion. In this regard, a remarkable toughened ZrO2 /MgO nanocomposite coating is obtained by the plasma electrolytic oxidation (PEO) process and in-situ synthesized ZrO2 with quantitative control approach. It is revealed that the toughening behavior of the ZrO2 /MgO coating is related to the coordination and diversion of lattice distortion at the metallic oxide interface, which induces distinct dislocation motion at the interface. The semicoherent interface between m-ZrO2 and MgO is verified to act as a buffer to realize toughening of the nanocomposite coating through dislocation slipping induced by lattice coordinated distortion. Simultaneously, significant interfacial lattice distortion transfer and dislocation pinning are discovered at the semicoherent interface between t-ZrO2 and MgO, which are beneficial to toughness enhancement of the nanocomposite coating. The results indicate that the toughening effect occurs along with dislocation slipping and pinning caused by lattice distortion of the ZrO2 /MgO semicoherent interface, which enables the toughness of novel nanocomposite coating to reach 2.7 times of the traditional PEO coating.